ANALISIS BREAK EVEN POINT PENJUALAN PUPUK KOMPOS TOAR ORGANIC FERTILIZER DI KAKASKASEN KOTA TOMOHON - Maya Basaria Sianipar; Juliana R. Mandei; Theodora M. Katiandagho (AGRI-SOSIOEKONOMI, 2016)
The purpose of this study was to analyze the value of sales of compos at break even. Starting from of 2012, 2013, 2014 and 2015. Analysis of break even point is an analysis tools that is used by management of a company that serves to determine the level of sales, so the company doesn’t profit and loss. Analysis of break even points can be used by a manager or a leader of the company with the aim to determine the level of sales volume before experiencing benefits and losses.Research uses the data analysis break even point. Research result shows that every year this business is able to obtain even a break even achieve a profit.